Meningkatkan Karakteristik Anak Melalui Program Ekstrakurikuler di Perumahan Buana Impian 2 Kota Batam - Wasiman, Wasiman; Wage, Sunarto; Fifi, Fifi; Wangdra, Yvonne; Wangdra, Ronald (PUAN INDONESIA, 2024)
Law Number 20 of 2003 regarding the National Education System Article 3 aims to enhance national intelligence and functions to shape the character of the Indonesian nation. According to Minister of Education and Culture Regulation Number 62 of 2014, extracurricular activities are those undertaken by students outside of regular school hours as part of intracurricular and co-curricular programs, under the guidance and supervision of educational institutions. These activities aim to fully develop students' potential, talents, interests, abilities, personalities, cooperation, and independence to support the achievement of national education goals. Common extracurricular activities in schools include scouting, sports (such as football and volleyball), arts (dance, music, theater), the Youth Red Cross (PMR), scientific projects, and Olympiads. Achievement indicators include the implementation of these extracurricular activities. According to literature, character education encompasses values education, moral education, and character education, all aimed at developing the abilities of all school members. Students' character formation can be achieved through various school activities and the involvement of teachers and parents in managing their children's activities at school and in the community. Education should not only aim to make children smart but also instill noble values or national character. Therefore, instilling these values must begin at an early age so that children grow up to be proud members of the nation. To address the decline in morals or character among students, innovations are needed to shape children's character and reduce moral crises. Regularly conducted extracurricular activities can shape children to adopt positive behaviors, while teachers can contribute through learning activities and by setting examples. Thus, it is recommended that schools conduct regular activities and provide adequate care, fostering cooperation between schools, school committees, and parents in monitoring each child's activities both at school and in the community through extracurricular activities.